Anti-apoptotic and growth-stimulatory functions of CK1 delta and epsilon in ductal adenocarcinoma of the pancreas are inhibited by IC261 in vitro and in vivo. Issue 6 (18th January 2008) - Brockschmidt, C; Hirner, H; Huber, N; Eismann, T; Hillenbrand, A; Giamas, G; Radunsky, B; Ammerpohl, O; Bohm, B; Henne-Bruns, D; Kalthoff, H; Leithäuser, F; et al.
Abstract : Background: Pancreatic ductal adenocarcinomas (PDACs) are highly resistant to treatment due to changes in various signalling pathways. CK1 isoforms play important regulatory roles in these pathways. Aims: We analysed the expression levels of CK1 delta and epsilon (CK1δ/∊) in pancreatic tumour cells in order to validate the effects of CK1 inhibition by 3-[2, 4, 6-(trimethoxyphenyl)methylidenyl]-indolin-2-one (IC261) on their proliferation and sensitivity to anti-CD95 and gemcitabine. Methods: CK1δ/∊ expression levels were investigated by using western blotting and immunohistochemistry. Cell death was analysed by FACS analysis. Gene expression was assessed by real-time PCR and western blotting. The putative anti-tumoral effects of IC261 were tested in vivo in a subcutaneous mouse xenotransplantation model for pancreatic cancer. Results: We found that CK1δ/∊ are highly expressed in pancreatic tumour cell lines and in higher graded PDACs. Inhibition of CK1δ/∊ by IC261 reduced pancreatic tumour cell growth in vitro and in vivo. Moreover, IC261 decreased the expression levels of several anti-apoptotic proteins and sensitised cells to CD95-mediated apoptosis. However, IC261 did not enhance gemcitabine-mediated cell death either in vitro or in vivo. Conclusions: Targeting CK1 isoforms by IC261 influences both pancreatic tumour cell growth and apoptosis sensitivity in vitro and the growth of induced tumours in vivo, thus providing a promising new strategy for the treatment of pancreatic tumours.